The Role of STAT1 for Crosstalk between Fibroblasts and Colon Cancer Cells - Kaler, Pawan; Owusu, Benjamin Y.; Augenlicht, Leonard; Klampfer, Lidija (Frontiers in Oncology, 2014)
Signaling between tumor cells and the associated stroma has an important impact on cancer initiation and progression. The tumor microenvironment has a paradoxical role in tumor progression and fibroblasts, a major component of the tumor stroma, have been shown to either inhibit or promote cancer development. In this study we established that normal intestinal fibroblasts activate STAT1 signaling in colon cancer cells and, in contrast to cancer- associated fibroblasts, inhibit growth of tumor cells. Treatment of 18Co fibroblasts with the proinflammatory cytokine TNF interfered with their ability to trigger STAT1 signaling in cancer cells. Accordingly, intestinal myofibroblasts isolated from patients with Ulcerative colitis (UC) or Crohn’s disease (CD), which are activated and produce high levels of TNF, failed to stimulate STAT1 signaling in tumor cells, demonstrating that activated myofibroblasts lose the ability to trigger growth-inhibitory STAT1 signaling in tumor cells. Finally, we confirmed that silencing of STAT1 in tumor cells alters the crosstalk between tumor cells and fibroblasts, suggesting STAT1 as a novel link between intestinal inflammation and colon cancer. We demonstrated that normal fibroblasts restrain the growth of carcinoma cells, at least in part, through the induction of STAT1 signaling in cancer cells. We showed that changes in the microenvironment, as they occur in inflammatory bowel disease, alter the crosstalk between carcinoma cells and fibroblasts, perturb the homeostasis of intestinal tissue and thereby contribute to tumor progression.